Combined Treatment With 2-(2-Benzofu-Ranyl)-2-Imidazoline and Recombinant Tissue Plasminogen Activator Protects Blood–Brain Barrier Integrity in a Rat Model of Embolic Middle Cerebral Artery Occlusion - Zhang, Linlei; Xu, Shasha; Wu, Xiaoxiao; Chen, Jiaou; Guo, Xiaoling; Cao, Yungang; Zhang, Zheng; Yan, Jueyue; Cheng, Jianhua; Han, Zhao (Frontiers in Pharmacology, 2020)
Recombinant tissue plasminogen activator (rt-PA) is used to treat acute ischemic stroke but is only effective if administered within 4.5 h after stroke onset. Delayed rt-PA treatment causes blood-brain barrier (BBB) disruption and hemorrhagic transformation. The compound 2-(-2-benzofuranyl)-2-imidazoline (2-BFI), a newly discovered antagonist of high-affinity postsynaptic N-methyl-D-aspartate (NMDA) receptors, has been shown to have neuroprotective effects in ischemia. Here, we investigated whether combining 2-BFI and rt-PA can ameliorate BBB disruption and prolong the therapeutic window in a rat model of embolic middle cerebral artery occlusion (eMCAO). Ischemia was induced in male Sprague Dawley rats by eMCAO, after which they were treated with 2-BFI (3 mg/kg) at 0.5 h in combination with rt-PA (10 mg/kg) at 6 or 8 h. Control rats were treated with saline or 2-BFI or rt-PA. Combined therapy with 2-BFI and rt-PA (6 h) reduced the infarct volume, denatured cell index, BBB permeability, and brain edema. This was associated with increased expression of aquaporin 4 (AQP4) and tight junction proteins (occludin and ZO-1) and downregulation of intercellular adhesion molecule 1 (ICAM-1) and matrix metalloproteinases 2 and 9 (MMP2 and MMP9). We conclude that 2-BFI protects the BBB from damage caused by delayed rt-PA treatment in ischemia. 2-BFI may therefore extend the therapeutic window up to 6 h after stroke onset in rats and may be a promising therapeutic strategy for humans. However, mechanisms to explain the effects oberved in the present study are not yet elucidated.